Nocardiosis Diseminada: Un Diagnóstico Inesperado - Inês Zão; Paulo Torres Ramalho (Sociedade Galega de Medicina Interna, 2020)
Nocardiosis is a rare opportunistic infection caused by the bacteria Nocardia spp. It may presents as a localized cutaneous infection or as an invasive infection (pulmonary, central nervous system or disseminated). The authors describe a 65-years-old woman, without a known cause of immunosuppression, admitted with fever, respiratory and constitutional symptoms. After an exhaustive etiological study, it was diagnosed a disseminated nocardiosis (pulmonary and central nervous system), in a probable context of immunosuppression secondary to a previously undiagnosed systemic lupus erythematosus. Nocardiosis is a serious infection with a variable and non-specific presentation making its diagnosis a challenge.